(untitled) (Педагогіка вищої та середньої школи, 2012)
У статті охарактеризовано творчість як важливу передумову змін у навчально-виховному процесі сучасної школи; розкрито сутність поняття «творча особистість»; висвітлено особливості та обґрунтовано педагогічні умови формування творчої особистості підлітка у навчально-виховному процесі загальноосвітньої школи України. Ключові слова: творчість, творча особистість, особистісна творчість, індивідуалізація, гуманізація, педагогічні умови. Іn the article we have characterised creativity as an important precondition for changes in the educational process in modern school; shown the essence of the notion of «creative personality»; grounded the peculiarities and educational conditions for forming a teenager’s creative personality at the educational process in secondary schools in Ukraine. Key words: creativity, creative personality, personal creativity, individualization, humanization, educational conditions.